2023
DOI: 10.3390/medicina59122156
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pre-Season and Relationships with Physical, Physiological, Body Composition, and Load Markers: A Case Study Comparing Starters versus Non-Starters from an Elite Female Professional Soccer Team

Rafael Oliveira,
João Paulo Brito,
Renato Fernandes
et al.

Abstract: Background and Objectives: Research on female soccer players that analyzes playing status is scarce and has previously only examined load monitoring, while other markers, such as physical (i.e., strength, power, and agility), physiological (i.e., maximal oxygen uptake), and body composition (i.e., body fat mass, fat-free mass, body water, and phase angle) markers, warrant further investigation. Thus, the study aims were to (a) compare physical, physiological, body composition, and load markers between starters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the first study showing the evolution of physical performance throughout an entire season in female football players. Most of the studies carried out so far are based on punctual determinations at one moment throughout a season [ 19 , 22 , 27 ]. Our study comprises a whole season of a total of 27 players from two teams playing in the same football category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study showing the evolution of physical performance throughout an entire season in female football players. Most of the studies carried out so far are based on punctual determinations at one moment throughout a season [ 19 , 22 , 27 ]. Our study comprises a whole season of a total of 27 players from two teams playing in the same football category.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other authors have reported significant declines in aerobic capacity and vertical jump from the preseason until the end of the season, although only two time points were measured [ 21 ]. A recent study conducted with elite female Portuguese football players did not find any improvement in physical performance following a 5-week training intervention [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation